Peningkatan Kualitas Air Bersih Melalui Optimalisasi Filter Guna Mengatasi Air Keruh dan Berbau di TPQ Nurul Huda - Heru Wahyu Herwanto; Sujito, Sujito; Triyanna Widyaningtyas; Abdullah Iskandar Syah; Muhammad Fazlur Rahman Addakhil (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2026)
TPQ Nurul Huda, located in Mayong Village, Karangbinangun Subdistrict, Lamongan Regency, is a religious educational institution that plays an important role in nurturing the younger generation through social and religious activities. This TPQ faces serious problems related to the availability of clean water. The well water used tends to be cloudy, discoloured, and smelly, causing discomfort for residents in meeting their household needs and worshipping. This community service activity aims to overcome these problems through the application of appropriate technology in the form of water filters. The methods used include surveying water conditions, designing and installing filters, training in operation, and maintenance of equipment, as well as testing and evaluating the filtration results together with the community. The results show a significant improvement in water quality, where water that was originally cloudy, discoloured, and odorous has become clear, odourless, and suitable for daily use. In addition, the community's skills in operating and maintaining the filters have also improved, so that this technology can be utilised independently and sustainably, while also contributing significantly to the comfort of worship and the health of the community.